Alternative Dispute Resolution (ADR): A Theoretical Framework in context of Nepal (Samsad Journal संसद जर्नल, 2025)
Conflict is an inevitable facet of human interaction, permeating various facets of society, from interpersonal relationships to complex business transactions. Traditional litigation processes, often associated with protracted timelines and exorbitant costs, May not always serve as the most efficient or satisfactory means of dispute resolution. This article examines into the realm of Alternative Dispute Resolution (ADR) as a pragmatic and increasingly popular approach to resolving conflicts. The literal meaning of ADR is the use of methods of mediation or an arbitration along with other alternative mechanism to the court to resolve a dispute without resort to the litigation. It is also known as an alternative mechanism to settle the disputes with an involvement of neutral third parties who tends to resolve the dispute neutrally. The objective of this article is to provide a comprehensive overview of ADR, its diverse methods, principles, various legal mechanisms to ADR and their applications across various sectors. This article also set out some of the prominent cases concerning ADR and its application. In addition, the article examines the advantages and limitations of ADR in contrast to traditional litigation, emphasizing the potential for cost savings, quicker resolutions, and preservation of relationships. This article reads for ADR to be a complimentary or an appropriate to the Court procedure in pacific settlement of the disputes instead of an alternative way to dispute settlement.